Changes in the structural and catalytic characteristics of α-amylase under moderate electric field. (September 2022) - Li, Dandan; Chen, Caiwen; Tao, Yang; Huang, Yi; Wang, Pei; Han, Yongbin
Abstract: The study aimed to investigate the effect of moderate electric field (MEF) on the performance of α-amylase in corn starch hydrolysis. MEF (1–12.5 V/cm, 50–350 Hz) was performed on α-amylase and/or corn starch under different conditions (0–50 mM Ca 2+ ; 40–70 °C; 10–120 min). As a pretreatment, low-intensity MEF (2.5 V/cm) did not induce the hydrolysis of native and fully gelatinized starch but increased the enzyme activity by 23% due to slight unfolding of α-amylase. Although more extensive hydrolysis was observed for fully gelatinized starch when the hydrolysis was performed by MEF-pretreated α-amylase (reducing sugar: 38.5 g/L, the control; 48.6 g/L, 2.5 V/cm; 51.2 g/L, 2.5 V/cm + 10 mM Ca 2+ ) and MEF treatment in the presence of α-amylase (42.2 g/L, the control; 48.1 g/L, 2.5 V/cm; 51.3 g/L, 2.5 V/cm + 10 mM Ca 2+ ), a small increase occurred for native starch. Overall, the results proved that substrate structure dominated in the enzymatic hydrolysis of starch under MEF, providing a guide for applying electro-based techniques in starch modification. Graphical abstract: Image 1 Highlights: Low-intensity moderate electric field (MEF) improved the activity of α-amylase. Enhanced enzyme activity was attributed to the changed conformation structure. Densely packed structure of starch dominated in MEF-assisted enzymatic hydrolysis. Extensive hydrolysis occurred for fully gelatinized starch under MEF. Minor hydrolysis happened for native starch under MEF.